2014
DOI: 10.1165/rcmb.2014-0021tr
|View full text |Cite
|
Sign up to set email alerts
|

The Crossroads of Iron with Hypoxia and Cellular Metabolism. Implications in the Pathobiology of Pulmonary Hypertension

Abstract: The pathologic hallmark of pulmonary arterial hypertension (PAH) is pulmonary vascular remodeling, characterized by endothelial cell proliferation, smooth muscle hypertrophy, and perivascular inflammation, ultimately contributing to increased pulmonary arterial pressures. Several recent studies have observed that iron deficiency in patients with various forms of PAH is associated with worsened clinical outcome. Iron plays a key role in many cellular processes regulating the response to hypoxia, oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 96 publications
2
34
0
Order By: Relevance
“…1 Moreover, it has been demonstrated that endurance training increases cytochrome c concentration in the presence of sufficient cellular iron resources, 31,32 providing a rationale for the higher training effects seen in NIS patients both in terms of ΔV'O2peak and percentage of responders to endurance training than NAID patients, as shown in this study.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…1 Moreover, it has been demonstrated that endurance training increases cytochrome c concentration in the presence of sufficient cellular iron resources, 31,32 providing a rationale for the higher training effects seen in NIS patients both in terms of ΔV'O2peak and percentage of responders to endurance training than NAID patients, as shown in this study.…”
Section: Discussionsupporting
confidence: 58%
“…1 Moreover, iron is an essential nutrient that plays a central role in cellular bioenergetics. Aerobic metabolism is critically dependent on iron-containing proteins, such as haemoglobin (Hb) and cytochrome c. The latter facilitates cellular oxygen utilization in the mitochondrial respiratory chain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We provided that iron restriction led a modest attenuation of hypoxiainduced pulmonary vascular remodeling in mice. Iron is reported to be associated with the pathogenesis of several cardiovascular diseases, including PH [9]. Moreover, disrupted pulmonary iron homeostasis has been reported in several chronic lung diseases [10].…”
Section: Discussionmentioning
confidence: 99%
“…Iron plays a critical role in oxygen transport and iron depletion affects regulation of hypoxia-inducible factors [3]. In a preclinical study, a reduction in iron and ferritin levels resulted in marked pulmonary vascular remodeling that was reversed by iron supplementation [4].…”
Section: Introductionmentioning
confidence: 99%